Pelatihan Keramahtamahan Berkonsep Omotenashi dalam Upaya Meningkatkan Kesadaran Berperilaku: Siswa SMK BOPKRI 1 - Teti Indriati Kastuti; Christine Dian Permatasari; Theresia Ninung Pandamnurani (Universitas Teknologi Yogyakarta, 2024)
This community service program aims to enhance the hospitality skills and awareness of BOPKRI High School students as future tourism professionals. Hospitality is crucial in the tourism industry as it affects the experience and satisfaction of tourists. The training includes the basic concepts of omotenashi, which encompass hospitality intelligence, emotional intelligence, linguistic intelligence, and kinesthetic intelligence. The training is conducted in three stages: planning, implementation, and evaluation. During the planning stage, group discussions are held to identify training needs. The implementation stage includes theoretical sessions and simulations. Evaluation is carried out through questionnaires, observations, and monitoring to measure the effectiveness of the training. The expected outcomes of this program are improved hospitality skills, increased awareness of friendly behavior towards guests, and enhanced tourist satisfaction. Additionally, this program aims to prepare students to become professional, ethical tourism practitioners who can adapt to various cultures and situations in the tourism industry.